(untitled) - Spear, Terry (Sourcebooks Casablanca, 2021)
"Heather MacNeil has never backed down from a fight. So when some shady shifters from a neighboring enemy clan come looking for trouble, she refuses to feed their satisfaction. Theres only one wolf that makes her go soft. For packmate Enrick MacQuarrie, the work as second- in-command never ends-as the feud ignites, clan security is more vital than ever. But a certain unpredictable, feisty Highland lass is determined to stand up to the aggressors, and Enrick is equally determined to protect her. The action builds as Heather and Enrick grow closer, but will they be willing to sacrifice their wild friendship for true love?"--Page 4 of cover.
Keywords: Castles; Production and direction; Motion pictures; Fiction; Shapeshifting; Fiction; Werewolves; Fiction; Fiction; Highlands (Scotland); Fiction; Paranormal Romance; Werewolf fiction; Romance fiction